2017
DOI: 10.1111/ajpy.12149
|View full text |Cite
|
Sign up to set email alerts
|

Predicting community attitudes towards asylum seekers: A multi‐component model

Abstract: Objective: The current study investigated the role of cognitive, affective, and behavioural information in the prediction of overall attitudes towards asylum seekers. Method: A sample of 98 Australian adults participated in an online self-report questionnaire where participants generated their cognitive, affective, and behavioural factors towards asylum seekers and then rated those factors on a continuum from 'positive' to 'negative'. Results: Multiple regression analysis confirmed the primary role of cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Past experiences have been investigated in few studies using The Tripartite Theory (Breen et al 2018;Croucamp et al 2017;Haddock and Zanna 1997). In our study, participants' experiences were moderately and significantly associated with their attitudes toward VAD.…”
Section: Discussionmentioning
confidence: 66%
“…Past experiences have been investigated in few studies using The Tripartite Theory (Breen et al 2018;Croucamp et al 2017;Haddock and Zanna 1997). In our study, participants' experiences were moderately and significantly associated with their attitudes toward VAD.…”
Section: Discussionmentioning
confidence: 66%
“…It draws attention that, the first studies with regard to the attitudes towards the asylumseekers/refugees were performed in the countries being most frequently applied by the asylumseekers/refugees, such as Canada, Australia, USA, South Africa (Gordon, 2016;Nickerson & Louis, 2008). It is emphasized in this study that, cognitive, affective, and behavioral factors stand out predominantly among those influencing the society's attitudes towards the refugees (Croucamp, O'Connor, Pedersen, & Breen (2017). Economic reasons (Christophersen, Liu, Thorleifsson, and Tiltnes, 2013;Ceobanu & Escandell, 2010), nationalism and misbeliefs (Pederson, Attwell & Heveli, 2005), safety, social harmony, cultural threat, and social dominance tendency (Nickerson & Louis, 2008) have been singled out the most in this respect among the factors affecting the attitude towards refugees.…”
Section: Introductionmentioning
confidence: 83%
“…A cross-sectional descriptive survey of community members across Australia was conducted using a validated survey template. 22…”
Section: Methodsmentioning
confidence: 99%
“…21 In a different area, it was reported that only beliefs underpinned community attitudes toward asylum seekers. 22…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation